PERANAN DISIPLIN KERJA DAN KESELAMATAN & KESEHATAN KERJA (K3) DALAM MENINGKATKAN KINERJA KARYAWAN - Faishal, Muhammad; Nuryanti, B Lena; Masharyono, Masharyono (Business Education Program of Universitas Pendidikan Indonesia, 2019)
The crisis of employee performance is a critical problem faced by management in the company. Employee performance problems are still widely faced by companies in various sectors in many countries, both engaged in the public and private sectors, in health institutions, education, banking, state-owned companies, to small companies. The low intensity and inaccessibility of work targets due to the low quality of the performance of human resources. Performance is a real behavior that is shown by every employee must be in accordance with his role in the company, that the impact of low employee performance is the quality and quantity of work produced is less satisfactory and the creativity of employees is low. This happened at PT XYZ company where the level of employee performance decreases every year. Surely this is far from the expectations of companies that ask their employees to have good performance. This study discusses research on work discipline and occupational safety health (k3) on employee performance This research uses quantitative methods involving 45 respondents using saturated samples with data collection techniques using questionnaires. The data analysis technique used is descriptive analysis. The results of this study indicate that the picture of work discipline in the high category, the picture of occupational safety and health (k3) in the category is quite high and the description of employee performance in the high category.